Requirement of phosphorus and its use efficiency by sunflower (Helianthus annuus L.) in high phosphorus soils: REQUIREMENT OF PHOSPHORUS AND ITS EFFICIENCY BY SUNFLOWER IN HIGH PHOSPHORUS SOILS - A MADHAVI,; P SURENDRA BABU,; P VENKATA REDDY, (Journal of Oilseeds Research, 2015)
Field experiments were conducted during kharif 2008, 2009 and 2010 to find out the phosphorus requirement to sunflower crop grown in a soil with high initial available phosphorus (110-119 kg P2O5/ha). Three years pooled data revealed that application of 100% recommended dose of P2O5(RDP) resulted highest seed yield of 12.18 q/ha. The seed yield increased significantly by about 9.51, 11.75, 12.50 and 13.62 per cent due to application of 25 (11.74 q/ha), 50 (11.98 q/ha), 75 (12.06 q/ha) and 100 (12.18 q/ha) per cent RDP, respectively over control (10.72 q/ha). However, the differences in seed yields observed at 50, 75 and 100% RDP are narrow and imperceptible. The per cent phosphorus derived from fertilizer (% Pdff) and phosphorus-use efficiency decreased significantly from 21.10 to 19.93 per cent and 24.19 to 6.67 per cent, respectively due to increase in P level from 25 to 100% RDP, whereas the fertilizer P uptake and soil P uptake increased from 1.58 to 1.75 kg/ha and 5.93 to 7.03 kg/ha, respectively with increase in P level from 25 to 100% RDP. The extent ofsaving in P fertilizer in these soils is ranged from 75 to 100 per cent depending upon the P build up in the soil.